GOOD FAITH VERSUS BAD FAITH IN MITIGATING THE COVID-19 PANDEMIC IN INDONESIA - Rissy, Yafet Yosafet Wilben (Universitas Brawijaya, 2023)
The COVID-19 pandemic has caused a real economic crisis across the globe, including Indonesia. To overcome this critical issue, the Indonesian President issued Government Regulation in Lieu of Law No. 1 of 2020 which was later stipulated as Law No. 2 of 2020 (the 2020 COVID-19 Emergency Law). This study applies a doctrinal legal research method. The result of the study shows that Article 17 of the 2020 COVID-19 Emergency Law grants the government officials the right of immunity to not be sued legally as long as their actions are in accordance with the good faith principle. Unfortunately, this law does not explain the meaning of good faith, so that it can become a grey area for the abuse of power. It is recommended that the government officials should be mindful in exercising their extraordinary powers based on the principle of good faith such as honesty, loyalty, trust, honour, a lack of fraudulent actions and conflict of interests, and adherence to the applicable laws to avoid an abuse of power and corruption in Indonesia.